A QUEST FOR ARTICULAR CARTILAGE PROGENITOR CELLS LEADS TO TEMPORAL REGULATION OF HYALURONAN REQUIRED FOR 3T3-L1 ADIPOGENESIS - Sellers, Samantha Sue (East Carolina University, 2017)
During embryogenesis, mesenchymal progenitor cells exhibit hyaluronan-dependent pericellular matrices as a major component of the extracellular matrix. As connective tissues form by cellular condensations, there is a loss of cell-associated hyaluronan to facilitate cell-to-cell adhesion. The goal of this dissertation is to gain insight into how hyaluronan-associated components of the extracellular/pericellular matrix participate in directing differentiation fates of mesenchymal cells. This work began with attempts to isolate and study a primary mesenchymal progenitor population from adult bovine articular cartilage and progressed to the use of the adipocyte-favoring mesenchymal progenitor cell line, 3T3-L1. A particle exclusion assay revealed that 3T3-L1 mesenchymal cells exhibited large hyaluronan-dependent pericellular matrices that were displaced by small hyaluronan fragments consisting of 6-8 disaccharides, suggesting retention of the matrix by a cell surface receptor. These pericellular matrices were enhanced with the addition of exogenous aggrecan (prepared from bovine articular cartilage). However, 3T3-L1 cells lost the ability to synthesize or retain a hyaluronan-dependent pericellular matrix during adipogenesis. We observed a reduction in mRNA and protein expression of CD44, the hyaluronan receptor that anchors the pericellular matrix to the cell surface, during adipogenesis, in addition to a reduction in mRNA expression of Has2 and Vcan. These reductions in pericellular matrix components are likely responsible for the loss of detectable pericellular matrix by 3T3-L1 adipocytes. The importance of CD44's role in pericellular matrix retention was further supported when pericellular matrices could not be formed by 3T3-L1 adipocytes even when exogenous hyaluronan and aggrecan were supplied. Hyaluronan was visualized by staining with a binding protein (HABP) and fluorescent microscopy. Mesenchymal cells exhibited bright cell surface HABP staining whereas adipocytes stained only weakly. However, when the adipocytes were permeabilized with 0.5% Triton-X, hyaluronan was revealed between the lipid droplets of these cells suggesting receptor-mediated endocytosis. When hyaluronan synthesis was blocked with 4-methylumbelliferone, adipogenesis of 3T3-L1 cells was significantly inhibited. Additionally, exogenous aggrecan added to the culture medium during the adipogenic differentiation protocol significantly inhibited adipogenesis. Collectively, these data suggest that 3T3-L1 adipogenesis is dependent upon the temporal regulation of hyaluronan.
Keywords: 3T3-L1 cells; aggrecan; extracellular matrix; Hyaluronic Acid; Adipogenesis; Cartilage, Articular; Stem Cells